2013
DOI: 10.4103/0972-124x.124534
|View full text |Cite
|
Sign up to set email alerts
|

Bdellovibrio bacteriovorus : A future antimicrobial agent?

Abstract: Bdellovibrio and like organisms (BALOs) are small, predatory, Deltaproteobacteria that prey on other Gram-negative pathogens. Many authors have unfolded the possible use of BALOs as biological control agents in environmental as well as medical microbiological settings. They are found strongly associated with natural biofilms and recent studies have shown that effective predation occurs in these naturally occurring bacterial communities. Periodontal infections could also be an interesting target for the applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 11 publications
(21 reference statements)
0
26
0
3
Order By: Relevance
“…They are found strongly associated with natural biofilms and recent studies have shown that effective predation occurs in these naturally occurring bacterial communities. Accordingly, recent researches aim to present the evolution toward applying Bdellovibrio as an antibacterial agent to deal with oral infections, general medical conditions, environmental, and industrial issues (El‐Shanshoury, Abo‐Amer, & Alzahrani, ; Harini, Ajila, & Hegde, ).…”
Section: Resultsmentioning
confidence: 99%
“…They are found strongly associated with natural biofilms and recent studies have shown that effective predation occurs in these naturally occurring bacterial communities. Accordingly, recent researches aim to present the evolution toward applying Bdellovibrio as an antibacterial agent to deal with oral infections, general medical conditions, environmental, and industrial issues (El‐Shanshoury, Abo‐Amer, & Alzahrani, ; Harini, Ajila, & Hegde, ).…”
Section: Resultsmentioning
confidence: 99%
“…), medicine (Harini et al . ), ecological security (Monnappa et al . ) and food hygiene (Atterbury et al .…”
Section: Introductionmentioning
confidence: 99%
“…Since their discovery in the early 1960s (Stolp and Petzold 1962), BALOs have received much attention because of their mysterious life style and novel ability to lyse prey cells. It was reported that BALOs have a great potential of both the promising bacterial strains of probiotics and an alternative to antibiotics in aquaculture (Zhou et al 2009;Cao et al 2012), medicine (Harini et al 2013), ecological security (Monnappa et al 2013) and food hygiene (Atterbury et al 2011). However, less information was provided on BALOs as a biocontrol agent of bacterial contamination in the culture of microalgae.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, predation of the pathogens can increase due to increased consumer densities 13 . However, this predation cannot eradicate the whole pathogen population 14 , 15 , which enables also future outbreaks.…”
Section: Introductionmentioning
confidence: 99%